Risk factors for the formation of gastroenterological pathology after infectious hemocolitis in children - O. I. Klimova; N. V. Gonchar; Yu. V. Lobzin; S. G. Grigorev (Детские инфекции (Москва))
The aim of the study was to determine the risk factors for the formation of gastroenterological pathology in convalescents of infectious hemocolites. In the Department of intestinal infections, 120 children aged over 1 month who had intestinal infections with hemocolitis syndrome were observed. The etiology of the disease was verified, clinical and laboratory signs of intoxication, dehydration, local and systemic inflammatory response were detected. Non-specific complications (respiratory diseases, urinary tract infection) were diagnosed. In the acute period of the disease, the composition of the intestinal microbiota was evaluated by PCR-RT. During 6 months, 65 convalescents were observed in the catamnesis. If there were complaints from the gastrointestinal tract, functional gastrointestinal disorders (FGID) were diagnosed. When «symptoms of anxiety» appeared, organic intestinal lesions were detected. When «symptoms of anxiety» appeared, organic intestinal lesions were detected. The results were evaluated using the student's test, the Mann-Whitney U-test, the Kruskal-Wallis test, the Pearson correlation method, and discriminant analysis. Studies have shown that there were 43 children with a favorable outcome (66.2%), 17 children with FGID (26.1%), and 5 children with organic intestinal lesions (7.7%). In patients who formed organic lesions, the bacterial etiology of hemocolitis was more often noted. Gastroenterocolitis was more often diagnosed in patients with a favorable outcome (41.9%; p > 0,05). Non-specific complications were more often observed in patients who formed FGID and organic lesions. The frequency of FGID decreased with age and was higher in girls (58.8%) than in boys (41.2%) (p > 0,05). Organic intestinal lesions were observed only in girls. In convalescents with FGID, more often (83.3%) than in convalescents with a favorable outcome (64.3%), signs of anaerobic intestinal imbalance were detected. A complex of clinical and laboratory signs of an acute period of infectious hemocolites that determine the risk of FGID formation has been established. It was shown that the risk of developing FGID is higher in young convalescents, and the risk of forming organic intestinal lesions is higher in girls of preschool and school age. Patients who showed more pronounced systemic inflammatory responses in the acute period of the disease were more likely to have a favorable outcome.